An integrative approach to infer systematic relationships and define species groups in the shrub frog genus Raorchestes, with description of five new species from the Western Ghats, India - Garg, Sonali; Suyesh, Robin; Das, Sandeep; Bee, Mark A.; Biju, S. D. (PeerJ, 2021)
The genus Raorchestes is a large radiation of Old World tree frogs for which the Western Ghats in Peninsular India is the major center for origin and diversification. Extensive studies on this group during the past two decades have resolved long-standing taxonomic confusions and uncovered several new species, resulting in a four-fold increase in the number of known Raorchestes frogs from this region. Our ongoing research has revealed another five new species in the genus, formally described as Raorchestes drutaahu sp. nov., Raorchestes kakkayamensis sp. nov., Raorchestes keirasabinae sp. nov., Raorchestes sanjappai sp. nov., and Raorchestes vellikkannan sp. nov., all from the State of Kerala in southern Western Ghats. Based on new collections, we also provide insights on the taxonomic identity of three previously known taxa. Furthermore, since attempts for an up-to-date comprehensive study of this taxonomically challenging genus using multiple integrative taxonomic approaches have been lacking, here we review the systematic affinities of all known Raorchestes species and define 16 species groups based on evidence from multi-gene (2,327 bp) phylogenetic analyses, several morphological characters (including eye colouration and pattern), and acoustic parameters (temporal and spectral properties, as well as calling height). The results of our study present novel insights to facilitate a better working taxonomy for this rather speciose and morphologically conserved radiation of shrub frogs. This will further enable proper field identification, provide momentum for multi-disciplinary studies, as well as assist conservation of one of the most colourful and acoustically diverse frog groups of the Western Ghats biodiversity hotspot.
Keywords: Anura; Bioacoustics; Biodiversity hotspot; Diagnostic characters; Eye colour; Integrative taxonomy; Molecular phylogeny; Morphology; Peninsular India; Rhacophoridae